The Dynamic Nexus of Digital Evolution, Environmental Turbulence and Environmental Performance: A Case of High-tech Industries in the Emerging 4th Industrial Revolution - Sinaga, Obsatar; Saudi, Mohd Haizam Mohd; Roespinoedji, Djoko; Razimi, Mohd Shahril Ahmad (International Journal of Energy Economics and Policy, 2019)
The aim of the current study lies in exploring the potential effect of environmental turbulence on environmental performance and digital evolution. Furthermore, the present study also aims to capture the fruitfulness of digitalization on sustainable environment in the emerging 4IR environment. In doing so, the statistical application of structural equation modelling leads to discover the all five variables have a significant impact on each other. Market turbulence and technological turbulence have positive and significantly impact on Environmental turbulence that confirming two hypotheses. Furthermore, environmental turbulence has a negative and significant impact on digital evolution and environmental performance. However, digital evolution has a positive and significantly impact on environmental performance in Malaysian small manufacturing enterprises. This model explains 63.80% variance of environmental performance by all the factors of Environmental turbulence and digital evolution. Therefore, the current study suggested to expand their horizon of intellect towards digital commerce as it underlies the potential to generate improved and effective environmental conditions. Keywords: 4th industrial revolution, environmental turbulence, environmental performance, Malaysia. JEL Classifications: Q55, Q50 DOI: https://doi.org/10.32479/ijeep.8363